The Importance of the Regional Species Pool, Ecological Species Traits and Local Habitat Conditions for the Colonization of Restored River Reaches by Fish - Stoll, Stefan (Public Library of Science, 2014)
It is commonly assumed that the colonization of restored river reaches by fish depends on the regional species pools; however, quantifications of the relationship between the composition of the regional species pool and restoration outcome are lacking. We analyzed data from 18 German river restoration projects and adjacent river reaches constituting the regional species pools of the restored reaches. We found that the ability of statistical models to describe the fish assemblages established in the restored reaches was greater when these models were based on ‘biotic’ variables relating to the regional species pool and the ecological traits of species rather than on ‘abiotic’ variables relating to the hydromorphological habitat structure of the restored habitats and descriptors of the restoration projects. For species presence in restored reaches, ‘biotic’ variables explained 34% of variability, with the occurrence rate of a species in the regional species pool being the most important variable, while ’abiotic’ variables explained only the negligible amount of 2% of variability. For fish density in restored reaches, about twice the amount of variability was explained by ‘biotic’ (38%) compared to ‘abiotic’ (21%) variables, with species density in the regional species pool being most important. These results indicate that the colonization of restored river reaches by fish is largely determined by the assemblages in the surrounding species pool. Knowledge of species presence and abundance in the regional species pool can be used to estimate the likelihood of fish species becoming established in restored reaches.